Identification of a novel clip domain serine proteinase (Sp-cSP) and its roles in innate immune system of mud crab Scylla paramamosain. Issue 1 (November 2015) - Sun, Wanwei; Li, Zhongzhen; Wang, Shasha; Wan, Weisong; Wang, Shuqi; Wen, Xiaobo; Zheng, Huaiping; Zhang, Yueling; Li, Shengkang
Abstract: Clip domain serine proteinases and their homologs are involved in the innate immunity of invertebrates. To identify the frontline defense molecules against pathogenic infection, we isolated a novel clip domain serine proteinase ( Sp -cSP) from the hemocytes of mud crab Scylla paramamosain . The full-length 1362 bp Sp -cSP contains a 1155 bp open reading frame (ORF) encoding 384 amino acids. Multiple alignment analysis showed that the putative amino acid sequence of Sp -cSP has about 52% and 51% identity with Pt- cSP2 (AFA42360 ) and Pt- cSP3 (AFA42361 ) from Portunus trituberculatus, respectively, while the similarity with other cSP sequences was lower than 30%. However, all cSP sequences possess a conserved clip domain at the N-terminal and a Tryp-SPc domain at the C-terminal. The genomic organization of Sp -cSP consists of nine exons and eight introns, with some introns containing one or more tandem repeats. RT-PCR results indicated that Sp -cSP transcripts were predominantly expressed in the subcuticular epidermis, muscle and mid-intestine, but barely detectable in the brain and heart. Further, Sp -cSP transcripts were significantly up-regulated after challenge with lipopolysaccharides (LPS), Vibrio parahaemolyticus, polyinosinic polycytidylic acid (PolyI:C) or white spot syndrome virus (WSSV). Moreover, in vitro, the recombinant Sp -cSP revealed a strong antimicrobial activity against a Gram-positive ( Staphylococcus aureus ) and four Gram-negative ( V. parahaemolyticus, Vibrio alginolyticus, Escherichia coli, Aeromonas hydrophila ) bacteria in a dose-dependent manner. Taken together, the acute-phase response to immune challenges and the antimicrobial activity assay indicate that Sp -cSP is a potent immune protector and plays an important role in host defense against pathogen invasion in S. paramamosain . Highlights: Full-length of Sp -cSP with 1362 bp was isolated from mud crab. Sp -cSP transcripts were significantly up-regulated after immune challenges. r Sp -cSP showed strong antimicrobial activities against pathogens.